MP-7 Isolation of Antibiotic Resistance Gene from Staphylococcus aureus from Chicken Poultry Farm in Bogor West Java Indonesia - Nabila Swarna Puspa Hermana; Agustin Indrawati; Fachriyan Hasmi Pasaribu (Hemera Zoa, 2018)
Staphylococcus aureus is an opportunistic pathogen in human and another animal species. It also associated with staphylococcosis, osteomyelitis, arthritis, and bumble foot disease in poultry. Antibiotics including penicillin, erythromycin and tetracycline are widely used for treating infection caused by S. aureus.Chicken poultry play important role in food supply as one of protein source in Indonesia. West Java province has largest population of chicken poultry, where Bogor has the largest population of chicken poultry with 19.75.850 chicken in 2018. In order to maintain the production, farmers used antibiotics for prophylaxis, growth promotor, and therapy. However, extensive use of antibiotic can be found in low income and developed country, caused the increasing number of antibiotic resistant bacteria.The aim of this study is to determine the antibiotic resistance pattern of S. aureus isolated from cloacal swab of chicken poultry in Bogor West Java Indonesia.